2021
DOI: 10.3389/fpls.2021.736421
|View full text |Cite
|
Sign up to set email alerts
|

Pepper Novel Pseudo Response Regulator Protein CaPRR2 Modulates Drought and High Salt Tolerance

Abstract: Plants modify their internal states to adapt to environmental stresses. Under environmental stress conditions, plants restrict their growth and development and activate defense responses. Abscisic acid (ABA) is a major phytohormone that plays a crucial role in the osmotic stress response. In osmotic stress adaptation, plants regulate stomatal closure, osmoprotectant production, and gene expression. Here, we isolated CaPRR2 – encoding a pseudo response regulator protein – from the leaves of pepper plants (Capsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…However, no ubiquitination activity was detected in the present study (Figure S8). On the other hand, we could observe the transcriptional activity in the anterior AN1‐like zinc finger domain (Figure 3d) and that CaSAP14 could activate the expression of stress‐responsive genes, including CaOSR1 and CaRAB18 , which are also induced by ABA or osmotic stress (Lim et al., 2022; Lim, Lim, & Lee, 2021; Park et al., 2016). These findings indicate that CaSAP14 can function as a transcription factor, not an E3 ligase, in pepper plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no ubiquitination activity was detected in the present study (Figure S8). On the other hand, we could observe the transcriptional activity in the anterior AN1‐like zinc finger domain (Figure 3d) and that CaSAP14 could activate the expression of stress‐responsive genes, including CaOSR1 and CaRAB18 , which are also induced by ABA or osmotic stress (Lim et al., 2022; Lim, Lim, & Lee, 2021; Park et al., 2016). These findings indicate that CaSAP14 can function as a transcription factor, not an E3 ligase, in pepper plants.…”
Section: Discussionmentioning
confidence: 99%
“…For physiological assays, namely, those for electrolyte leakage and the contents of proline and MDA, the roots of 4‐week‐old pepper plants were soaked in 200 m m NaCl for 16 h, and 2‐week‐old Arabidopsis plants were subjected to 250 m m NaCl solution for the same time. Thereafter, the leaves of pepper and Arabidopsis plants were collected for the respective assays, as previously described (Bae et al., 2021; Lim, Lim, & Lee, 2021; Luo et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have identified CaPRR2 in pepper plants as the PRR2 homolog gene and characterized its negative role in osmotic stress tolerance (Lim et al, 2021). The expression levels of CaPRR2…”
Section: Discussionmentioning
confidence: 99%
“…In plants, the precise biological functions of the PRR genes in responses and Arabidopsis APRR5/APRR7 are involved in ABA signaling (Lim et al, 2021, Yang et al, 2021. Here, we investigated the role of pseudo-response regulator SlSRP1 in tomato plants using the VIGS system and elucidated that SlSRP1 has a negative effect on ABA-mediated osmotic stress responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation